Penjelasan dengan langkah-langkah:
|x - 1| = |x + 7|
(x - 1)² = (x + 7)²
(x - 1)² - (x + 7)² = 0
((x - 1) + (x + 7))((x - 1) - (x + 7) = 0
(x - 1 + x + 7)(x - 1 - x - 7) = 0
(2x + 6)(-8) = 0
(2x(-8) + 6(-8)) = 0
-16x - 48 = 0
-16x = 0 + 48
-16x = 48
x = 48/-16
x = -3
HP{-3}
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Penjelasan dengan langkah-langkah:
|x - 1| = |x + 7|
(x - 1)² = (x + 7)²
(x - 1)² - (x + 7)² = 0
((x - 1) + (x + 7))((x - 1) - (x + 7) = 0
(x - 1 + x + 7)(x - 1 - x - 7) = 0
(2x + 6)(-8) = 0
(2x(-8) + 6(-8)) = 0
-16x - 48 = 0
-16x = 0 + 48
-16x = 48
x = 48/-16
x = -3
HP{-3}